Value Engineering for the Selection of the Filler Material between Shoring Wall and the Structure - Atabay, Senay (UNIV OSIJEK, TECH FAC, 2021)
In the traditional construction projects, project shareholders develop their projects rather by taking the cost into consideration after the occurrence of the need. The companies should focus on quality, cost and speed in the projects they carry out to be able to keep up in the competitive environment. Value engineering is the revision of the new or existent products at the design stage for the purpose of increasing the value of the product, decreasing the cost and increasing the functionality. In this study, it has been tried to decide which material / method should be selected to be able to fill the space between a shoring wall and the structure with the use of Value Engineering Method. Firstly, a value engineering team has been formed; it has been decided which needs the material / method should meet, solutions that could provide these needs have been sought and it has been decided to compare three determined alternative solutions. Afterwards, value analysis has been conducted and the solution that can meet the need both in terms of quality and cost has been tried to be selected. In this way, economically most convenient solution has been determined without neglecting the requests of the customers and the benefit to be attained. As a result of the Value Engineering study, it was concluded that Alternative 2b (making waste mold with profile and 15 mm oriented strand board) is the most suitable solution.
Keywords: construction management; geotechnical engineering; selection of material; shoring wall; value analysis; value management; PROJECT; Engineering